Ovulatory Follicular Dynamics After Estrus Synchronization Using Intravaginal Progesterone Implant in Dairy Cows - Prabowo Purwono Putro (Jurnal Sain Veteriner, 2013)
Abstract The study aimed to follow ovulatory follicular dynamics and plasma progesterone profile after estrus synchronization using progesterone intravaginal implant CIDR and its combination with PGF2a and GnRH. A total of 15 non-pregnant dairy cows, 4-5 years of age, healthy and reproductively sound were divided into 3 treatment groups. Treatment 1, CIDR implant was inserted intravaginally for 9 days (CIDR); treatment 2, given CIDR and 250 mg GnRH intramuscularly at implant removal (CIDR + GnRH); treatment 3, CIDR and 25 mg PGF2a at day 7 of implant insertion (CIDR + PGF2a). Transrectal ultrasonographic examination using real time, B-mode, with 7.5 MHz transducer was performed everyday for 12 days to follow ovulatory follicular dynamics. Blood plasma was taken every day for progesterone determination using EIA technique. Data were tested using analysis of variance and correlation analysis. The result indicated that CIDR implant was a potent agent for estrus synchronization with the onset of estrus was 66.18 + 03.42 hours after its removal. The addition of GnRH resulted the highest ovulatory growth rate following the implant removal (1.67 + 0.17a, 1.93 + 0.13b dan 1.53 + 0.20a mm/day, P < 0.05). Insertion of CIDR hampered dominant follicular development and its removal caused rapid follicular growth and followed by ovulation. Its insertion resulted steady increase in plasma progesterone levels and its removal resulted in sudden decrease in the hormonal levels, induced ovulatory follicular development, followed by estrus and ovulation. The CIDR implant also inhibited luteal growth, caused no effect of PGF2a administration on decrease of plasma progesterone levels. Addition of GnRH at the time of CIDR removal enhanced the highest rate of ovulatory follicular growth.